2015
DOI: 10.3390/md13074436
|View full text |Cite
|
Sign up to set email alerts
|

Low Molecular Weight Fucoidan Inhibits Tumor Angiogenesis through Downregulation of HIF-1/VEGF Signaling under Hypoxia

Abstract: Activation of hypoxia-induced hypoxia-inducible factors-1 (HIF-1) plays a critical role in promoting tumor angiogenesis, growth and metastasis. Low molecular weight fucoidan (LMWF) is prepared from brown algae, and exhibits anticancer activity. However, whether LMWF attenuates hypoxia-induced angiogenesis in bladder cancer cells and the molecular mechanisms involved remain unclear. This is the first study to demonstrate that LMWF can inhibit hypoxia-stimulated H2O2 formation, HIF-1 accumulation and transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(95 citation statements)
references
References 31 publications
1
92
0
2
Order By: Relevance
“…Chen et al showed that a low molecular weight fucoidan (LMWF) obtained from Sargassum hemiphyllum ( M w = 760 g/mol, 40% sulfate) dose-dependly reduced hypoxia effect on VEGF-induced capillary tube-like structure formation in Human Umbilical Endothelial Cells (HUVEC) in vitro, and did not affect angiogenesis under normoxic condition [33]. In addition, they showed that LMWF treatment inhibited the migration and invasion of hypoxic Human Bladder Cancer Cells (T24).…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al showed that a low molecular weight fucoidan (LMWF) obtained from Sargassum hemiphyllum ( M w = 760 g/mol, 40% sulfate) dose-dependly reduced hypoxia effect on VEGF-induced capillary tube-like structure formation in Human Umbilical Endothelial Cells (HUVEC) in vitro, and did not affect angiogenesis under normoxic condition [33]. In addition, they showed that LMWF treatment inhibited the migration and invasion of hypoxic Human Bladder Cancer Cells (T24).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to cancer therapy, fucoidan appears to be highly efficient in treating certain types of cancer, including breast, prostate and lung, as well as leukemia (10)(11)(12). Furthermore, fucoidan can also play a crucial role in inhibiting induced cancer signaling molecules, such as vascular endothelial growth factor (VEGF) (13,14). Although these results support the potential development of fucoidan as an anticancer drug, there is little information on the anticancer effect of fucoidan on colorectal cancer (CRC).…”
Section: Furthermore We Provide Evidence For the Therapeutic Applicamentioning
confidence: 99%
“…Several studies have demonstrated that fucoidan induces cancer cell death through mitochondrial abnormalities, including increased production of mitochondrial reactive oxygen species (21), inhibits tumor angiogenesis via down-regulation of HIF1 and VEGF (14), down-regulates cell cycle-regulated kinase (22)…”
Section: Fucoidan-mediated Inhibition Of Cell Viability and Cell Prmentioning
confidence: 99%
“…Przeprowadzone dotychczas badania nad przeciwnowotworowymi właściwościami fukoidyny wykazały jej zdolność do hamowania angiogenezy w obrębie nowotworu [13,15,16,31,41]. Liu i wsp.…”
Section: Angiogenezaunclassified
“…Badania prowadzone nad właściwościami fukoidyny pozyskanej z alg z gatunku Sargassum hemiphyllum wykazały jej zdolność do hamowania wzrostu guza i angiogenezy in vivo poprzez obniżanie aktywacji HIF-1α stymulowanej hipoksją, ekspresji VEGF i wewnątrzkomórkowego tworzenia reaktywnych form tlenu w komórkach raka pęcherza linii T24. Ponadto nie obserwowano spadku masy ciała zwierząt traktowanych fukoidyną, co świadczy o jej dobrej tolerancji [16].…”
Section: Angiogenezaunclassified